2014
DOI: 10.3791/52059
|View full text |Cite|
|
Sign up to set email alerts
|

Larval RNA Interference in the Red Flour Beetle, <em>Tribolium castaneum</em>

Abstract: The red flour beetle, Tribolium castaneum, offers a repertoire of experimental tools for genetic and developmental studies, including a fully annotated genome sequence, transposon-based transgenesis, and effective RNA interference (RNAi). Among these advantages, RNAi-based gene knockdown techniques are at the core of Tribolium research. T. castaneum show a robust systemic RNAi response, making it possible to perform RNAi at any life stage by simply injecting double-stranded RNA (dsRNA) into the beetle's body c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The RNAi response in T. castaneum is one of the strongest and sustained in insects tested to date 42 . RNAi in both adult and larva beetles is systemic and can be triggered by injection of dsRNA in any tissue or stage 43 . Despite this already substantial reaction, we demonstrated that the effect of RNAi can be increased further by employing a nanostructured delivery agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNAi response in T. castaneum is one of the strongest and sustained in insects tested to date 42 . RNAi in both adult and larva beetles is systemic and can be triggered by injection of dsRNA in any tissue or stage 43 . Despite this already substantial reaction, we demonstrated that the effect of RNAi can be increased further by employing a nanostructured delivery agent.…”
Section: Discussionmentioning
confidence: 99%
“…T. castaneum larvae were size and age sorted and held in flour/bran media at 28 °C/80% RH prior to trials (adapted from Linz et al 43 ). Larvae were restrained using strips of adhesive tape at the anterior and posterior ends and microinjected in the dorsal side of the abdominal segments using heat-pulled micro-capillary borate silicon needles with a bore size of ~ 25 µm in conjunction with a Nanoject II system (Harvard Apparatus, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The dsRNAs were diluted to a concentration of 1 μg/μl with T. castaneum injection solution (Linz et al, 2014). Then, 100 nl of the solution (100 ng/larva) was injected into the haemocoel at the dorsal side of the thorax of sixth instar T. castaneum larvae using a Nanoliter 2010 injector with a MICRO4 Controller (World Precision Instruments, Sarasota, FL, USA), and the injected larvae were reared under the conditions indicated.…”
Section: Injected Rnaimentioning
confidence: 99%
“…Using this transcriptome, we synthesized dsRNAs from template cDNAs of the Dalotia coriaria white (Dcw) and vermillion (Dcver) loci, which have been shown to control eye pigmentation in beetles (46,47). We developed an RNAi protocol based on the systemic larval RNAi method used in Tribolium (48)(49)(50)(51).…”
Section: Potent Gene Knockdown Using Larval Rnai In Dalotiamentioning
confidence: 99%